When Do UN Peacekeeping Operations Implement Their Mandates?. Issue 3 (28th July 2021) - Blair, Robert A.; Di Salvatore, Jessica; Smidt, Hannah M.
Abstract: Under what conditions do UN peacekeeping operations (PKOs) implement the tasks in their mandates? Contemporary PKOs are expected to fulfill increasingly fragmented mandates in active conflict zones. We argue that these two trends—increasingly fragmented mandates, increasingly implemented amidst violence—exacerbate delegation and coordination problems that hinder PKOs from pursuing mandated tasks, potentially undermining their legitimacy in the eyes of the Security Council, troop‐contributing countries, and host governments. Combining new data sets on PKO activities and mandates in Africa (1998–2016) and using instrumental variables and two‐way fixed effects models, we find that mandate fragmentation is negatively correlated with mandate implementation, especially for peacebuilding tasks. Ongoing violence is also negatively correlated with implementation of peacebuilding tasks, but not with security tasks. We show that this is likely due to the offsetting effects of violence perpetrated by governments and rebels, as PKOs are better equipped to respond to the latter.